Significance of CEA Stain and PyNPase Stain for Hematogenous Metastasis from Colorectal Cancer - Sakuyama, T.; Takamura, S. (Nippon Daicho Komonbyo Gakkai Zasshi, 2000)
To evaluate predictive factors for hematogenous metastasis from colorectal cancer, we performed immunohistochemical study using CEA stain and PyNPase stain of surgical speciemens from 100 patients with colorectal cancer including 50s with hematogenous metastasis and 50s without metastasis. Univariate analysis showed multiple important factors which were tumor size, tumor depth, venous invasion, lymph node metastasis, CEA stain and PynPase stain. But multivariate analysis disclosed, the most significant factor was PyNPase stain (p=0.0007, Odds ratio: 14.75), and the 2nd significant factor was distribution of CEA stain (p=0.0085, Odds ratio: 5.71). These observations suggest that these immunochemical stainings were important predictive factors for hematogenous metastasis from colorectal cancer.